A Meta-Analysis of Risk Factors for the Formation of de novo Intracranial Aneurysms. Issue 4 (30th July 2018) - Hu, Si; Yu, NianZu; Li, YiYun; Hao, Zheng; Liu, Zheng; Li, Mei-hua
Abstract: BACKGROUND: Understanding the risk factors for the formation of de novo intracranial aneurysms (IAs) is important for patients who have ever suffered a cerebral aneurysm. OBJECTIVE: To estimate the risk factors for the development of a de novo IA to identify which patients need more aggressive surveillance after aneurysm treatment. METHODS: We followed the preferred reporting items for systematic reviews and meta-analyses guidelines and searched the PubMed, CENTRAL, EMBASE, and LILACS databases using the key words cerebral aneurysms, de novo, IAs, risk factors combined using and/or. The search was performed in July 2017.We calculated odds ratios (ORs) and 95% confidence intervals (CIs) using RevMan 5.3 (Cochrane, London, United Kingdom) to evaluate risk factors. Statistical significance was set at P < .05. RESULTS: The analysis included 14 studies involving 6389 patients, of whom 197 patients had de novo IAs. The main risk factors for formation included sex (OR = 1.82, 95% CI [1.30, 2.56], P  = .0005, female vs male), age <40 yr (OR = 2.96, 95% CI [1.76, 4.96], P  < .0001), family history (OR = 2.05, 95% CI [1.07, 3.93], P  = .03), smoking history (OR = 2.73, 95% CI [1.81, 4.12], P  < .0001), and multiple saccular intracranial aneurysms (sIAs) at first diagnosis (OR = 2.10, 95% CI [1.12, 3.91], P  = .02), internal carotid artery (ICA) as the initial site (OR = 2.58, 95% CI [1.43, 4.68], P  = .002). Heterogeneous analysis showed that these I 2 were less than 50% and the results were reliable. CONCLUSION: Observational evidence identified multiple clinical and anatomic risk factors for the formation of de novo IAs, including female sex, age <40 yr, family history, smoking history, multiple sIAs at first diagnosis, and IC as the initial site. More aggressive long-term angiographic follow-up with digital subtraction angiography, computed tomography angiography, or magnetic resonance angiography is recommended for these patients.